PROXIMATE COMPOSITION AND MEAT QUALITY STUDIES OF SOME EDIBLE FAUNA (Biological Sciences - PJSIR, 2002)
Meat samples of 15 different edible animal species from fish, birds  and  mammals  were  collected  for  laboratory  studies from Multan. It was observed  that % water was found  to be 75.41 ± 2.75, 72.52 ±     1.5, 74.34 ± 2.37; % fat 2.61± 0.44, 3.01± 0.47, 2 .76 ± 0.67; % protein 20 . 93 ±  5.97, 23.54 ±  1 .31, 22.03 ±  1.77; % ash 2.41 ± 2.74, 0.93 ± 0.26, 0.89 ± 0.16  i ncatfish, birds and mammals respectively when expressed  on  wet weight  basis.  ANOVA  revealed  that  among  fish , birds and mammals the % water, % fat and % protein content were found to be similar (P>0.05). Percent ash was significantly  higher in catfish than bi rds and mammals  (P